Corporate Financial Distress, Restructuring, and Bankruptcy : Predict and Avoid Bankruptcy, Analyze and Invest in Distressed Debt. - Altman, Edward I. (John Wiley & Sons, Incorporated, 2019)
A comprehensive look at the enormous growth and evolution of distressed debt markets, corporate bankruptcy, and credit risk models This Fourth Edition of the most authoritative finance book on the topic updates and expands its discussion of financial distress and bankruptcy, as well as the related topics dealing with leveraged finance, high-yield, and distressed debt markets. It offers state-of-the-art analysis and research on U.S. and international restructurings, applications of distress prediction models in financial and managerial markets, bankruptcy costs, restructuring outcomes, and more.